Testing the differential effects of acceptance and attention-based psychological interventions on intrusive thoughts and worry. (April 2017) - Ainsworth, B.; Bolderston, H.; Garner, M.
Abstract: Background: Worry is a key component of anxiety and may be an effective target for therapeutic intervention. We compared two psychological processes (attention and acceptance) on the frequency of intrusive worrying thoughts in an experimental worry task. Method: 77 participants were randomised across three groups and completed either a 10 min attention or acceptance-based psychological exercise, or progressive muscle relaxation control. We subsequently measured anxiety, and the content and frequency of intrusive thoughts before and after a 'worry induction task'. Results: Groups did not differ in baseline worry, anxiety or thought intrusions. Both attention and acceptance-based groups experienced fewer negative thought intrusions (post-worry) compared to the relaxation control group. The acceptance exercise had the largest effect, preventing 'worry induction'. Increases in negative intrusive thoughts predicted subjective anxiety. Discussion: We provide evidence that acceptance and attention psychological exercises may reduce anxiety by reducing the negative thought intrusions that characterise worry. Graphical abstract: Highlights: We used an experimental worry task to see how psychological interventions can target worry. We compared 10-min attention and acceptance-based exercises to progressive muscle relaxation. Both acceptance and attention were better than relaxation, and acceptance had the largest effect. Increases in negative intrusive thoughts predicted subjective anxiety across all groups. Acceptance and attention psychological exercises may help anxiety by reducing worry.